Novel Advances in Cell-Free Therapy for Premature Ovarian Failure (POF): A Comprehensive Review - Yahyavi, Yahya; Kheradi, Niloufar; Karimi, Abbas; Ebrahimi-Kalan, Abbas; Ramezani, Fatemeh; Yousefi, Soudabe; Teymouri Nobari, Shirin; Sadrekarimi, Hourieh; Nouri, Mohammad; Edalati, Mahdi (Advanced pharmaceutical bulletin, 2024)
Premature ovarian failure (POF), is a condition characterized by the early decline of ovulation function. POF is a complex disorder that can be caused by various factors, and the idiopathic form represents a significant proportion of POF patients. Hormone replacement therapy (HRT) is currently considered the first-line treatment for POF. This review aims to provide a comprehensive overview of recent advancements in platelet-rich plasma (PRP), in vitro activation (IVA), stem cell therapy, exosome therapy, microRNAs, and mitochondrial targeting therapies as a promising cell-free therapeutic approach in reproductive medicine. PLT-Exos, a new generation of cells, has been used to treat POF for more than a decade and has been shown to attenuate oocyte morphology and promote the differentiation of theca cells through the upregulation of PI3K/Akt and Bcl2, as well as the downregulation of the Smad and Bax signaling pathways. This review summarizes the current state of the art in the field of PLT-Exos and discusses the advantages and limitations of their potential clinical applications.